Effect of season, year and initial liveweight on liveweight gain and feeding efficiency in Western Sudan Baggara cattle - Khidir, O A El; Ibrahim, Salwa E (The Indian Journal of Animal Sciences, 2012)
Sudan Baggara cattle (2 152) in 30 batches of fattening feedlots from 1992 to 1994 were studied. They were fed molasses concentrate and sorghum straw offered at different levels. The data collected were pooled and analyzed according to the level of concentrate intake, year of fattening and initial liveweight for least-squares means of variance using GLM method. Concentrate level, year of fattening season and concentrate level x year interaction significantly affected average daily gain (APG) and feed conversion efficiency. Initial liveweight and season x initial liveweight interaction were significant for ADG. The results obtained showed that diets based on high level of molasses with sorghum straw are comparable with conventional diets for fattening local zebu cattle.